2018
DOI: 10.1080/21645515.2018.1496765
|View full text |Cite
|
Sign up to set email alerts
|

Predicting behavioral intentions to children vaccination among Chinese parents: an extended TPB model

Abstract: Parental behavioral intentions play a key role in children vaccination. The present study looks at how parental expectations for the vaccination influence their attitudes and behavioral intentions toward children's immunization. The theoretical model is developed on TPB model and empirically tested with sample data from 380 children aged 0-7 years in mainland China. The structural equation modeling and multi-group analysis were used in the model to demonstrate the impact of the vaccination services quality, va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
2
8
2
Order By: Relevance
“…A similar finding was revealed by Heena et al ( 57 ) that the health professionals' attitudes toward breast cancer screening can positively influence their decision to adopt this method. Moreover, some researchers ( 58 , 59 ) have considered AB to be a strong predictor of BI in the TPB model; thus, this may be an effective approach to focus on the benefits of performing CCSSs among primary care physicians. Based on the results of this survey, positive beliefs such as cost savings due to CCSSs, a sense of self-fulfillment and satisfaction were significant motivators for the intention to provide CCSSs.…”
Section: Discussionmentioning
confidence: 99%
“…A similar finding was revealed by Heena et al ( 57 ) that the health professionals' attitudes toward breast cancer screening can positively influence their decision to adopt this method. Moreover, some researchers ( 58 , 59 ) have considered AB to be a strong predictor of BI in the TPB model; thus, this may be an effective approach to focus on the benefits of performing CCSSs among primary care physicians. Based on the results of this survey, positive beliefs such as cost savings due to CCSSs, a sense of self-fulfillment and satisfaction were significant motivators for the intention to provide CCSSs.…”
Section: Discussionmentioning
confidence: 99%
“…We discovered that the square roots of AVE values were greater that these coefficients, which indicates that the discriminant validity of the scale meets the requirements for analysis. 48 …”
Section: Resultsmentioning
confidence: 99%
“…Vaccine safety was found to have a significant direct effect on trust towards the success of the COVID-19 vaccination program (H8). Following a previous study on child vaccination, it concluded that vaccine safety is one of the most critical factors affecting parents' intention to participate in childhood immunization programs (Zhou et al, 2018). Another study found that half of China's citizens delayed accepting the COVID-19 vaccine until it was confirmed to be safe (Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 97%